2014
DOI: 10.1111/anu.12148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different feed stimulants on freshwater crayfish (Procambarus clarkii), fed diets with or without partial replacement of fish meal by biofeed

Abstract: The feeding trials were carried out with freshwater crayfish (Procambarus clarkii) to evaluate the three feed stimulants betaine (Bet), squid extract (SE) and squid meal (SM) upon fish meal (FM) diets or biofeed (BF) diets in which FM were partially replaced by BF. Results showed the three feed stimulants had no significant effect on growth. By the relative concentration of markers in the faeces and diets, the preference for each diet was estimated, and the best stimulant was the mixture of Bet, SE and SM. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Feeding stimulants, which do not necessarily have a dietary value but modify the flavour of feed, are sometimes used in fish feed to improve palatability and increase FI. Numerous studies have demonstrated that some specific compounds like L‐amino acids, betaine (Bet) analogues, nucleotides and marine extracts are potent FS in aquatic feed (Hua et al., ; Johnson & Atema, ; Lall & Tibbetts, ; Luo, Tan, Liu, & Wen, ; Nakajima, ). Bet [(CH 3 ) 3 N + CHCOOH] has been proven as efficient FS or attractant for fish (Luo et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding stimulants, which do not necessarily have a dietary value but modify the flavour of feed, are sometimes used in fish feed to improve palatability and increase FI. Numerous studies have demonstrated that some specific compounds like L‐amino acids, betaine (Bet) analogues, nucleotides and marine extracts are potent FS in aquatic feed (Hua et al., ; Johnson & Atema, ; Lall & Tibbetts, ; Luo, Tan, Liu, & Wen, ; Nakajima, ). Bet [(CH 3 ) 3 N + CHCOOH] has been proven as efficient FS or attractant for fish (Luo et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Red swamp crayfish ( Procambarus clarkii ) is now widely cultured in China because of the delicious taste and high consumer demand (Hua et al., ). Studies on nutrient requirements, dietary energy to protein ratios, plant protein utilization and diet formulation of this crayfish have been conducted (Huner, ; Huner & Meyers, ; Jover, Fernández‐Carmona, Del Rı́o, & Soler, ; Reigh, Braden, & LaPrarie, ; Wiernicki, ; Xu, Wang, Wang, & Peng, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on nutrient requirements, dietary energy to protein ratios, plant protein utilization and diet formulation of this crayfish have been conducted (Huner, ; Huner & Meyers, ; Jover, Fernández‐Carmona, Del Rı́o, & Soler, ; Reigh, Braden, & LaPrarie, ; Wiernicki, ; Xu, Wang, Wang, & Peng, ). Although soybean meal shows higher protein and energy digestibility for red swamp crayfish (Reigh, Braden, & Craig, ), the palatability and attractiveness of diet decreased once fish meal in the diet of red swamp crayfish was replaced by alternative protein sources (Hua et al., ). Information regarding the inclusion of soybean meal and rapeseed meal as well as crystalline amino acid in the feed for red swamp crayfish is still limited known.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the palatability of diets have shown crustaceans will increase their feeding when particular stimulants are added to their diet (Harpaz et al, 1987;Hua et al, 2015). Crustacean species within aquaculture have preferences for specific textures and softness of food items (Cox and Johnston, 2003).…”
Section: Palatabilitymentioning
confidence: 99%
“…Several studies have examined feeding and nutrition requirements of captive-bred crayfish, including P. leniusculus (Carral et al, 2011;González et al, 2012), red swamp crayfish Procambarus clarkii (Hua et al, 2015) and common yabby Cherax destructor (Austin et al, 1997). Commercially available fish-feed pellets were historically fed to all age-classes resulting in low survival rates of hatchlings in both A. pallipes (Sáez-Royuela et al, 2001) and P. leniusculus (Ulikowski et al, 2006;Sáez-Royuela et al, 2007).…”
Section: Introductionmentioning
confidence: 99%